Application of Self-Adhesive Soft Silicone Common Foam Dressing in Reducing Intraoperative Pressure Ulcers in Elderly ICU Patients. (10th December 2021) - Wang, Fen; Gan, Xiaoqing; Zhou, Xu; Shen, Yanbing; Zhang, Ruiying; Hong, Sun; Tang, Dan; li, Sha; Shi, Zeya
Abstract : Pressure ulcer (PU), also called pressure injury, is localized damage to the skin and underlying soft tissues, usually over bony prominences, as a result of sustained mechanical loads applied to the tissues. However, in many situations, complete off-loading of sacral PUs is not possible. Minimising the exposure of wounds and their surroundings to elevated mechanical loads is crucial for healing. We for the first time reported the application of Meipicang in the prevention and treatment of intraoperative pressure ulcers in elderly ICU patients with severe illness. We found that the pressure ulcer risk score (20.15 ± 2.17 ) in the dressing group after intervention was higher than that (17.42 ± 3.62 ) in the regular group. The incidence of pressure sores in the dressing group was 3.77% lower than the 18.88% in the regular group. The psychological concern score (31.41 ± 3.15 ) of the dressing group was higher than that (26.92 ± 3.43 ) of the regular group. The trust score (29.57 ± 2.61 ) of the dressing group was higher than the score (24.28 ± 2.29 ) of the regular group. The score of physiological problems in the dressing group (34.69 ± 3.82 ) is higher than that in the regular group (29.88 ± 3.54 ). The skin complication rate of the dressing group was 5.56% lower than that of the regular group (22.64%). The comfort score (92.46 ± 4.15) of the dressing group was higher than that (80.59 ± 5.43 ) of the regular group. The nursing satisfaction score (94.53 ± 3.72 ) of the dressing group was higher than that (81.79 ± 4.61 ) of the regular group. To conclude, in this study, we found that the Meipicang dressing can reduce the incidence of pressure ulcers in ICU patients with severe ICU and improve the comfort and nursing satisfaction of elderly ICU patients with severe ICU, which is worthy of promotion.